A New Literacy: The Role of Technology to Develop Student’s Character - Eka Apriani (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2016)
Literacy is very important in human life since by being literate, people will be able to gain information. This paper discusses about the changing of old literacy to a new literacy. This changing brings effects to many aspects of life including in education. This paper shows how a new literacy which is known by ICT (information and communication technology) can develop student’s character. This new ICT has positive and negative effects. The counters only focus on explaining the positive effect of technology that is to build and improve the trustworthy, respect, diligence, responsibility, and courage. Building good student’s character can create good future leadership. Because of that student’s should be equipped with the ability of code-breaking, making- meaning, text-using, and text-analyzing. At the end, all parties (government, teachers, parents, etc) have to collaborate to use ICT in order to improve the quality of our education. Literasi sangat penting dalam kehidupan manusia karena dengan menjadi melek, orang akan dapat memperoleh informasi. Makalah ini membahas tentang perubahan literasi lama ke literasi baru. Perubahan ini membawa efek ke banyak aspek kehidupan termasuk dalam bidang pendidikan. Makalah ini menunjukkan bagaimana literasi baru yang dikenal dengan ICT (teknologi informasi dan komunikasi) dapat mengembangkan karakter siswa. ICT baru ini akan memiliki efek positif dan negatif. Kami hanya fokus pada menjelaskan efek positif dari teknologi itu adalah untuk membangun dan meningkatkan kepercayaan, menghormati, ketekunan, tanggung jawab, dan keberanian. Membangun karakter siswa yang baik dapat menciptakan pemimpin masa depan yang baik. Sehubungan dengan itu siswa harus dilengkapi dengan kemampuan pemecahan kode, memaknai hasil, menggunakan teks, dan analisis teks. Pada akhirnya, semua pihak (pemerintah, guru, orang tua, dan lain-lain) harus berkolaborasi untuk menggunakan ICT dalam rangka meningkatkan kualitas pendidikan kita.